A Systems Biology Driven Approach to Map the EP300 Interactors Using Comprehensive Protein Interaction Network - Kandegalla, Shivananda; Grishina, Mariana; Potemkin, Vladimir; Shekarappa, Sharath Belenehalli; Gollapalli, Pavan (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2020: Anais do XIII Simpósio Brasileiro de Bioinformática, 2020)
EP300 is one of the putative tumor-suppressor genes and is mutated/deleted, under expressed/overexpressed in several types of cancer. The role of EP300 and its interactions during cancer is crucial to explore its reprogramming events that lead to malignant phenotype and acquisition of drug resistance. In this context, all the experimentally valid EP300 interactors were collected from the primary protein-protein interaction (PPI) databases and followed by tracing their subcellular location using the UniProtKB database. Further, all the EP300 interactors were categorized based on their subcellular location and functionally annotated with the DAVID gene ontology tool. Subsequently, the interactome of EP300 with its interactors was constructed and identified TP53, CREBBP, JUN, HDAC1, CTNNB1, MYC, PCNA, HDAC2, FOS, and KAT2B as the top first neighbors of EP300. Together, the present analysis gives a comprehensive overview on EP300 interactors located in different subcellular locations.